SPECIFIC MAGNETIC STRUCTURE FORMING IN POLYMER NANOCOMPOSITES CONTAINING MAGNETITE NANOPARTICLES - Gendler T.S.; Novakova A.A.; Smirnov E.V. (My University, 2005)
The specific distribution of Fe3O4 nanoparticles synthesized in situ in a polymeric PVA matrix was studied using the methods of magnetic measurements, transmission and depth-selective Mössbauer spectroscopy, and tunnel microscopy. The magnetic nanoparticles volumetric concentration Cv varied in the study samples from 0.6 vol. % to 43 vol. %. The size of the nanoparticles, measured using the X-ray diffraction, was found to be 10-20 nm. In the case of low Cv values the nanoparticles showed the composition of maghemite. At growing Cv concentrations, the product of the synthesis was partially oxidized magnetite. The contribution of the particles participating in the magnetic interaction at room temperature was estimated from the hyperfine magnetic splitting of the Mössbauer spectra. The blocking temperatures of the films of all compositions were found to be in the region of 300° C. This study revealed the high planar and linear magnetic anisotropy of the remanent saturation magnetization and of the remanent laboratory synthesis magnetization (LSM). The Mössbauer and microscopic studies revealed that during the synthesis the particles are distributed in the nanocomposite irregularly over the matrix, remaining almost isolated at the surface of the films and producing, in the lower part of the film, the chains of interacting nanoparticles, extending parallel to the film plain along the resulting trend. This chain structure is treated here as an artificial analog of fossil bacterial structures and biofilms, contributing to the magnetization of sedimentary rocks.
Keywords: MAGNETIC NANOPARTICLES; THIN FILMS; MAGNETIC PROPERTIES; MAGNETIC ANISOTROPY